Correlation of prognosis and cost-effectiveness of computed tomography for out-of-hospital cardiac arrest patients with return of spontaneous circulation in the Emergency Department - Korkmaz, Tanzer; Asli Sener; Vermi Degerli (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the prevalence of computed tomography application in out-of-hospital cardiac arrest cases during emergency department processes, its contribution to changes in patient management, and effects on hospital discharge, and its cost-effectiveness. Method: The retrospective study was conducted at the Izmir Bakircay University Cigli Training and Research Hospital, Izmir, Turkey, and comprised data of adult out-of-hospital cardiac arrest patients who were brought to the emergency department and survived for at least 24 hours between June 21, 2016, and December 31, 2018. Demographic variables and computed tomography results were collected and analysed. Abnormalities found in computed tomography results that could have changed patient management, discharge results, and the cost of the computed tomography were recorded. Results: Of the 109 patients, 65(59.6%) were men with a mean age of 62.1± 14.2 years (range: 28-95 years), and the mean age of the 44(40.3%) female patients was 69.2 ± 15.8 years (range: 18-96 years). Overall, 74(67.9%) patients underwent computed tomography in the emergency department after resuscitation. Acute abnormalities were found in 4(3.6%) scans, and 3(2.7%) abnormal scans resulted in management changes. Conclusion: Computed tomography of out-of-hospital cardiac arrest patients in the emergency department should not be a matter of routine, and the scan, if necessary, should be done post-admission. Key Words: Out-of-hospital cardiac arrest, Return of spontaneous circulation, Computed tomography, Emergency medicine. Continue...